A GIS-Based Analysis of the Public Open Space Distribution and Accessibility in Gurugram City, India - Asmita Kanav; Jitendra Kumar (Forum Geografi)
The rapid pace of urbanization and increasing urban density in India has led to critical concern about the sustainability and livability of urban environments. In the city of Gurugram, public open spaces (POS) like parks and playgrounds are limited, highlighting the problem regarding their availability and accessibility. This study analyzes the current distribution of POS in the city of Gurugram at the ward level and compares the existing situation with national planning guidelines. It also aims to identify the population served by POS and the areas deficit in POS provision. The analysis reveals a deficit in per-capita POS at the city level, which stands at 3.14 m2 and shows high variability across different wards. A significant gap in the provision of housing area and neighborhood level POS was observed. The accessibility index calculated using Geographic Information System (GIS) based network analysis, reveals uneven access patterns across the city, with five wards lacking POS accessibility for residents, located primarily in central and southern-central areas. None of the wards of the city had all of its area serviced by POS, and only six wards had above 50 percent of the population residing in area serviced. These findings emphasize the need for strategic interventions to ensure universal access to POS, aligning with the sustainable development goals for urban areas.